Prognostic value of neutrophil to lymphocyte ratio in patients with esophagus cancer receiving neoadjuvant therapy: a systematic review and meta-analysis - Ma, Longwei; He, Jiaxing; Li, Ping; Ma, Long; Wang, He; Deng, Yanchao (Frontiers in Immunology, 2025)
BackgroundGrowing research reveals a relation of the neutrophil-to-lymphocyte ratio (NLR) to clinical outcomes of the esophageal cancer (EC) population undergoing neoadjuvant therapy. However, current findings remain inconclusive and somewhat controversial.MethodsPubMed, Embase, Web of Science, and the Cochrane Library were thoroughly retrieved until April 22, 2025 to collect studies on the link of NLR to prognosis among the EC population following neoadjuvant therapy. Eligible studies were selected as per predefined eligibility criteria. The primary outcomes encompassed overall survival (OS), recurrence-free survival (RFS), and pathological complete response (pCR). Hazard ratios (HRs) and corresponding 95% confidence intervals (CIs) were pooled for prognostic significance assessment along with subgroup analyses. The evidence was graded via the GRADE method.Results11 cohort studies involving 2,220 patients were included in the analysis. The results demonstrated a notable link of risen NLR to less favorable OS (HR = 1.99, 95% CI: 1.43–2.76, P < 0.0001; I² = 88%), shorter RFS (HR = 2.69, 95% CI: 1.77–4.08, P < 0.00001; I² = 47%), and lower pCR rates (OR = 0.67, 95% CI: 0.47–0.94, P = 0.02; I² = 62%). Subgroup analyses by sample size, follow-up length, age, treatment modality, and NLR cut-off value consistently demonstrated a strong correlation between elevated NLR and shortened RFS across all subgroups. Notably, in patients receiving neoadjuvant chemoradiotherapy (NCRT), the link of increased NLR to OS and RFS appeared more robust compared to those receiving neoadjuvant chemotherapy (NCT) alone.ConclusionIn patients with EC undergoing neoadjuvant therapy, a higher pre-treatment NLR is significantly linked to worse OS and RFS, as well as a lower likelihood of achieving pCR. Therefore, NLR can be a valuable prognostic biomarker in this patient population, potentially aiding clinicians in risk stratification and treatment decision-making.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024610088.